The role of the hydrophobic group on ring a of chalcones in the inhibition of interleukin-5 - Yang, Hyun-Mo; Shin, Hye-Rim; Cho, Soo-Hyun; Song, Gyu-Yong; Lee, In-Jeong; Kim, Mi-Kyeong; Lee, Seung-Ho; Ryu, Jae-Chun; Kim, Youngsoo; Jung, Sang-Hun (PHARMACEUTICAL SOC KOREA, 2006)
Novel chalcones were found as potent inhibitors of interleukin-5 (II-5). 1-(6-Benzyloxy-2-hydroxyphe nyl)-3-(4-hydroxyphenyl) propenone (2a, 78.8 % inhibition at 50 M, IC50 = 25.3 mu M) was initially identified as a potent inhibitor of IL-5. This activity is comparable to that of budesonide or sophoricoside (1a). The benzyloxy group appears to be critical for the enhancement of the IL-5 inhibitory activity. To identify the role of this hydrophobic moiety, cyclohexyloxy (2d), cyclohexylmethoxy (2c), cyclohexylethoxy (2e), cyclohexylpropoxy (2f), 2-methylpropoxy (2g), 3-methylbutoxy (2h), 4-methylpentoxy (2i), and 2-ethylbutoxy (2j) analogs were prepared and tested for their effects on IL-5 bioactivity. Compounds 2c (IC50 = 12.6 mu M), 2d (IC50 = 12.2 mu M), and 2i (IC50 = 12.3 mu M) exhibited the most potent activity. Considering the cLog P values of 2, the alkoxy group contributes to the cell permeability of 2 for the enhancement of activity, rather than playing a role in ligand motif binding to the receptor. The optimum alkoxy group in ring A of 2 should be one that provides the cLog P of 2 in the range of 4.22 to 4.67.
Keywords: AIRWAY HYPERRESPONSIVENESS; SOPHORICOSIDE ANALOGS; MOLECULAR-CLONING; IL-5; EOSINOPHILIA; HYPERREACTIVITY; EXPRESSION; RECEPTORS; BINDING